Disruption of a Plasmodium falciparum Multidrug Resistance-associated Protein (PfMRP) Alters Its Fitness and Transport of Antimalarial Drugs and Glutathione - Raj, Dipak Kumar (American Society for Biochemistry and Molecular Biology, 2009)
ATP-binding cassette transporters play an important role in drug resistance and nutrient transport. In the human malaria parasite Plasmodium falciparum, a homolog of the human p-glycoprotein (PfPgh-1) was shown to be involved in resistance to several drugs. More recently, many transporters were associated with higher IC(50) levels in responses to chloroquine (CQ) and quinine (QN) in field isolates. Subsequent studies, however, could not confirm the associations, although inaccuracy in drug tests in the later studies could contribute to the lack of associations. Here we disrupted a gene encoding a putative multidrug resistance-associated protein (PfMRP) that was previously shown to be associated with P. falciparum responses to CQ and QN. Parasites with disrupted PfMRP (W2/MRPΔ) could not grow to a parasitemia higher than 5% under normal culture conditions, possibly because of lower efficiency in removing toxic metabolites. The W2/MRPΔ parasite also accumulated more radioactive glutathione, CQ, and QN and became more sensitive to multiple antimalarial drugs, including CQ, QN, artemisinin, piperaquine, and primaquine. PfMRP was localized on the parasite surface membrane, within membrane-bound vesicles, and along the straight side of the D-shaped stage II gametocytes. The results suggest that PfMRP plays a role in the efflux of glutathione, CQ, and QN and contributes to parasite responses to multiple antimalarial drugs, possibly by pumping drugs outside the parasite.